2019
DOI: 10.31458/iejes.544742
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reward and Job Satisfaction toward Turnover Intention Private Junior High School

Abstract: The problem of teacher turnover, especially private teachers is a quite worrying in Indonesia and other developing countries. The high rate of teacher turnover will disrupt the achievement of educational goals. The main objective of this study was to see the effect of reward and job satisfaction on teachers' turnover intentions. This study uses a quantitative approach with a survey method. The sample of the study was all private junior high school teachers in Rokan Hulu District, consisting of 235 people selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…The effect of income on job satisfaction was consistent with previous studies that found a similar effect (Takei et al, 2009;Yang et al, 2008), and the effects of income on turnover intention were also consistent with findings in previous studies (Fakunmoju et al, 2010;Liu et al, 2019). In fact, findings from the parallel multiple mediation model are consistent with a recent finding suggesting that reward indirectly influenced turnover intention through its effects on job satisfaction (Hardianto et al, 2019): 'There is a direct negative effect of rewards on turnover intention, and there is a direct negative effect of job satisfaction on turnover intention and lastly there is a direct positive effect of reward on job satisfaction' (p. 128). Financial incentives appear to be a good motivation for job performance, which has implications for increasing employees' satisfaction about their jobs and reduces their propensity to leave their jobs.…”
Section: Associations Among Demographic Characteristics Job Satisfaction Life Satisfaction and Turnover Intentionsupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of income on job satisfaction was consistent with previous studies that found a similar effect (Takei et al, 2009;Yang et al, 2008), and the effects of income on turnover intention were also consistent with findings in previous studies (Fakunmoju et al, 2010;Liu et al, 2019). In fact, findings from the parallel multiple mediation model are consistent with a recent finding suggesting that reward indirectly influenced turnover intention through its effects on job satisfaction (Hardianto et al, 2019): 'There is a direct negative effect of rewards on turnover intention, and there is a direct negative effect of job satisfaction on turnover intention and lastly there is a direct positive effect of reward on job satisfaction' (p. 128). Financial incentives appear to be a good motivation for job performance, which has implications for increasing employees' satisfaction about their jobs and reduces their propensity to leave their jobs.…”
Section: Associations Among Demographic Characteristics Job Satisfaction Life Satisfaction and Turnover Intentionsupporting
confidence: 91%
“…Results from global research suggested that women were more likely than men to be satisfied with their lives (Joshanloo & Jovanović, 2020) and married women were more likely than men to be satisfied with their lives (Botha & Booysen, 2013). Similarly, income was found to be associated with job satisfaction (Takei et al, 2009; Yang et al, 2008) and turnover intention (Fakunmoju et al, 2010) and to influence turnover intention indirectly through effects on job satisfaction (Hardianto et al, 2019). A recent study found income to be associated with turnover intention and concluded that job satisfaction decreased the effects of job stress on turnover intentions (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…However, the variables of job satisfaction have also been examined from other perspectives. For example, reward is found to have a positive effect on private junior high school teachers' job satisfaction (Hardianto et al, 2019).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…In addition to the cultural intelligence of the managers, the job satisfaction of the employees is also related to their intention to leave (Gun et al, 2021;Hardianto et al, 2019;Yucel & Kocak, 2018). According to Mobley et al (1978), low job satisfaction can activate the intention to leave, lead to the evaluation of alternatives, and ultimately result in the behavior of intention to leave.…”
Section: Introductionmentioning
confidence: 99%
“…These orientations shape their expectations, wishes, behaviors, and job satisfaction perceptions in business life. When these expectations and wishes of teachers, which are influenced by their culture, are not met, teachers' job satisfaction is negatively affected, which can negatively affect their thoughts and attitudes towards work and trigger their intention to leave (Hardianto et al, 2019). As a result of all these, the school turns into an organization whose teachers are not satisfied with their jobs and whose teachers have intention to leave.…”
Section: Introductionmentioning
confidence: 99%